Exchange Values. Suggestions foran Ethical Formation of Personal Freedom - Innerarity, Daniel (1999)
The A. examines the question about the crisis of values under the light of the so-called postmaterialistic values and the ethics of care. Social individualization does not necessarily dissolve values but confers them a new form, which, such as the space of the promise, originates in the capacity of binding oneself freely. Thus, one shapes asort of security distance regarding oneself, thanks to which the immediate desire is overcome, other sirrupt in our valuations, and the wisdom of deception is found.